The importance of patients' case-mix for the correct interpretation of the hospital fatality rate in COVID-19 disease. (November 2020) - d'Arminio Monforte, Antonella; Tavelli, Alessandro; Bai, Francesca; Tomasoni, Daniele; Falcinella, Camilla; Castoldi, Roberto; Barbanotti, Diletta; Mulè, Giovanni; Allegrini, Marina; Tesoro, Daniele; Tagliaferri, Gianmarco; Mondatore, Debora; et al.
Highlights: We describe the importance of patients's characteristics and comorbidities in the outcome of COVID-19 disease. We point out two different waves of epidemics in Lombardy, the first one in younger and the second in older patients. Careful assessment of local setting in which COVID-19 spreads is needed to forsee fatality rates and hospital engagement. Abstract: Objective: We aimed to document data on the epidemiology and factors associated with clinical course leading to death of patients hospitalised with COVID-19. Methods: Prospective observational cohort study on patients hospitalised with COVID-19 disease in February-24th/May-17th 2020 in Milan, Italy. Uni-multivariable Cox regression analyses were performed. Death's percentage by two-weeks' intervals according to age and disease severity was analysed. Results: A total of 174/539 (32.3%) patients died in hospital over 8228 person-day follow-up; the 14-day Kaplan–Meier probability of death was 29.5% (95%CI: 25.5–34.0). Older age, burden of comorbidities, COVID-19 disease severity, inflammatory markers at admission were independent predictors of increased risk, while several drug-combinations were predictors of reduced risk of in-hospital death. The highest fatality rate, 36.5%, occurred during the 2nd–3rd week of March, when 55.4% of patients presented with severe disease, while a second peak, by the end of April, was related to the admission of older patients (55% ≥80 years) with less severe disease, 30% coming from long-term care facilities. Conclusions: The unusual fatality rate in our setting is likely to be related to age and the clinical conditions of our patients. These findings may be useful to better allocate resources of the national healthcare system, in case of re-intensification of COVID-19 epidemics.